Mid-level Managers, Organizational Context, and (Un)ethical Encounters - Dean, Kathy Lund; Beggs, Jeri Mullins; Keane, Timothy P. (2010)
This article details day-to-day ethics issues facing MBAs who occupy entry-level and mid-level management positions and offers defined examples of the stressors these managers face. The study includes lower-level managers, essentially excluded from extant literature, and focuses on workplace behaviors both undertaken and observed. Results indicate that pressures from internal organization sources, and ambiguity in letter versus spirit of rules, account for over a third of the most frequent unethical situations encountered, and that most managers did not expect to face those issues. Various contextual factors accounted for 32% of the organizational factors that affected decisions. We discuss implications for the workplace, especially the unique ethics challenges for newer managers.
Keywords: ethical context; entry-level manager; Ethical Climate; MBA ethics; ethical decision-making; Unethical behaviors; Ethics